Morphological differentiation of Carollia brevicauda and C. perspicillata (Chiroptera: Phyllostomidae) from Peru and Ecuador - Ruelas, Dennisse (2017)
In the bat genus Carollia, C. brevicauda and C. perspicillata are the most abundant and widely distributed in South America; also, their distributional ranges are almost completely overlapped. Because these species are morphologically very similar, they are frequently misidentified. The aims of this study were to determine the morphological and morphometric differences of C. brevicauda and C. perspicillata. For that reason, I employed a detail morphological assessment and several multivariate morphometric tools. I evaluated 26 normally craniodental variables in 375 adult specimens from Peruvian and Ecuadorian populations. In addition, 54 specimens of C. benkeithi, C. manu, and Carollia sp. were included for comparisons. I found that C. brevicauda and C. perspicillata are differentiated by 28 discrete characters, and are significantly different in 25 morphometric variables. Also, C. brevicauda, C. perspicillata, and C. manu are clustered in a different group from the group of C. benkeithi and Carollia sp. My results complement previous studies adding several characters that confidently differentiate C. brevicauda from C. perspicillata; which needs to be tested in other regions.